Smoking Bans and their Potential Implications for Mental Healthcare. A Review of the Evidence (2012)
UNLABELLED: Different publications have described a close relation between tobacco consumption and major psychiatric disorders. A great number of countries have enacted smoking bans in public or working places since the early 2000s; nonetheless, concerns remain over the exemption in some psychiatric settings regarding smoking bans. Admission of smokers to smoke-free units may lead to behavior deterioration, but some recent evidence refutes this argument.METHODS: Literature review.RESULTS: One of the earliest smoking bans was a 1.575 Mexican ecclesiastical council ban aimed at smoking prevention in churches. Several recent studies have documented health and economic benefits related to smoking bans. Over 83 countries now have introduced different sorts of regulations. There was no increase in aggression, seclusion or discharge against medical advice, neither increased use of PRN (as needed) medication following the ban. As part of the ban imposition, Nicotine Replacement Therapy- NRT was used by patients. Consistency, coordination and full staff support for the ban were seen as key success factors. Many patients continued smoking after discharge.CONCLUSIONS: Evidence shows that smoking has no place in psychiatric hospitals or facilities. The introduction of smoking bans in psychiatric settings is possible, but these bans must be conceived only as part of a much larger strategy, necessary to diminish smoking high rates among mental health populations.